Tools to Measure Oxygen Concentration and Oxygen Flow Rate in Continuous Positive Airway Pressure - Ade Putra; Tri Bowo Indrato; Liliek Soetjiatie (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2019)
Measuring oxygen concentration and measuring the flow of oxygen is a tool used to measure the percentage of oxygen content and oxygen flow rate in CPAP. This tool uses the OCS-03F sensor, with Arduino NANO processors then displayed on the 2X16 character LCD. Measuring the percentage of oxygen content and oxygen flow rate is carried out on CPAP for 5 measurements. The research and manufacture of this module uses the Pre-experimental method with the After Only Design design, which examines the